Diagnosis and treatment of dural carotid–cavernous fistulas: a consecutive series of 27 patients. Issue 2 (6th October 2006) - Théaudin, M; Saint-Maurice, J-P; Chapot, R; Vahedi, K; Mazighi, M; Vignal, C; Saliou, G; Stapf, C; Bousser, M-G; Houdart, E
Abstract : Objectives: To report clinical characteristics, angiographical findings and results of endovascular treatment of patients presenting with dural carotid–cavernous fistulas (DCCFs). Method: Retrospective analysis of 27 consecutive patients with DCCF referred to a specialised interventional neuroradiology department. Results: Orbital and neuro-ophthalmological symptoms were the most common clinical presentation at diagnosis (n = 25). The venous drainage of the fistula involved the ipsilateral superior ophthalmic vein in 24 patients, the contralateral cavernous sinus in 6 and a leptomeningeal vein in 5 patients. Thrombosis of at least one petrosal sinus was found in 23 patients. 7 patients did not receive endovascular treatment: 3 had spontaneous DCCF obliteration, and 4 had only minor clinical symptoms and no leptomeningeal venous drainage on an angiogram. 20 patients received endovascular treatment via either a transvenous (n = 16) or a transarterial approach (n = 4). Complete occlusion of the fistula was obtained in 14 of 16 (87%) patients treated by the transvenous approach and in 1 of 4 (25%) patients treated by the transarterial approach. 16 patients had early clinical improvement after endovascular treatment. One patient had a cerebral haemorrhage after transvenous embolisation of a DCCF with leptomeningeal drainage. On follow-up, all patients treated by the transarterial route remained symptomatic, whereas 10 of 14 (71%) patients cured by the transvenous route were asymptomatic. Conclusions: Transvenous embolisation is a safe and efficient endovascular approach to treat patients with DCCF. However, this technique requires a long learning curve.